Smart Irrigation System - Zainal Abidin, Mohammad Hakimi; Yasrizal, Muhammad Akmal Hariz; Mahadzir, Nur Alieya Natasha; Supar, Khairi (Multidisciplinary Applied Research and Innovation, 2025)
Malaysia is located on the equator where the areas along this line experience a tropical climate characterized by high temperatures throughout the year and receiving the most sunlight year-round. The issue of excessive heat inside homes for residents in inland areas remains a persistent problem until now. This study aims to develop a water flow system that uses renewable energy sources that could reduce heat in the house due to solar radiation and at the same time includes a hydroponic plant cultivation system. To address these issues, it is necessary to identify the components necessary to create a system capable of performing various functions known as a Smart Irrigation System (SIS). The Smart Irrigation System will optimize water usage by cycling water flow from roofs to plants, directing it to water tanks, and then redistributing it back onto the roofs. Solar panels are utilized to collect energy during the daytime, and the water passing through turbines generates kinetic energy, serving as a support for solar panels during the nighttime. Water pouring onto roofs can not only reduce indoor temperatures, but the availability of a continuous water cycle can also prevent excessive consumption of water for plants. Therefore, this Smart Irrigation System was built for those experiencing heat-related issues and it is significant for the following research on renewable energy sources, hydroponic system, water usage and many more.